Panitia Seminar Nasional Kimia - Nanang Tri Widodo (PROSIDING SEMINAR KIMIA, 2022)
Pengarah Dr. Eng. Idris Mandang, M.SiProf. Dr. Bohari, M.Si Penanggung Jawab Dr. Sri Wahyuningsih, M.SiDr. Yanti Puspita Sari, M.SiDr. Rudi Kartika, M.Si Ketua Moh. Saiful Arif, S.Pd. M.Si Sekretaris Djihan Ryn Pratiwi, M.Si Siti Maisarah, S.Pd BendaharaDr. Winni Astuti, M.Si Anggota Dr. Saibun Sitorus, M.SiDr. Subur P. Pasaribu, M.SiDr. Ir. Erwin, M.Si Dr. Chairul Saleh, M.SiDr. Ritbey Ruga, M.P., Ph.DAlimuddin, M.Si Ritson Purba, M.SiHusna Syaima, M.SiIrfan Ashari Hiyahara, M.Si Veliyana Londong A, M.SiIka Yekti Lianasari, M.SiRita Hairani, M.ScNanang Tri Widodo, M.SiAhmad Maulana, S.SiMuhammad Fadlianur, S.SiArbain Wawinca, SERahman Raya, S.PdManja’a Khasanah,S.Si